Improvement of in Vivo Quantification of [I]-Iodobenzovesamicol in Single-Photon Emission Computed Tomography/Computed Tomography Using Anatomic Image to Brain Atlas Nonrigid Registration - Frederic Lamare; Joachim Mazere; Mathieu Attila; Willy Mayo; Henri De Clermont-Gallerande; Wassilios Meissner; Philippe Fernandez; Michele Allard (Molecular Imaging)
Brain anatomy variability is a major problem in quantifying functional images in nuclear medicine, in particular relative to aging and neurodegenerative diseases. The aim of this study was to compare affine and elastic model–based methods for magnetic resonance imaging (MRI) to brain atlas registration and to assess their impact on the quantification of cholinergic neurotransmission. Patients with multiple system atrophy (MSA) and age-matched healthy subjects underwent an MRI and a single-photon emission computed tomographic (SPECT) examination using [ 123 I]-iodobenzovesamicol (IBVM). Both affine and elastic methods were compared to register the subjects' MRI with the Montreal Neurological Institute brain atlas. Performance of the registration accuracy was quantitatively assessed and the impact on the IBVM quantification was studied. For both subject groups, elastic registration achieved better quantitative performance compared to the affine model. For patients suffering from neurogenerative disease, this study demonstrates the importance and relevance of MRI to atlas registration in quantification of neuronal integrity. In this context, in comparison with rigid registrations, an elastic model–based registration provides the best relocation of the brain structures to the atlas for accurately quantifying cholinergic neurotransmission.